2019
DOI: 10.1111/gcb.14589
|View full text |Cite
|
Sign up to set email alerts
|

Carbon consequences of drought differ in forests that resprout

Abstract: Prolonged drought and intense heat‐related events trigger sudden forest die‐off events and have now been reported from all forested continents. Such die‐offs are concerning given that drought and heatwave events are forecast to increase in severity and duration as climate change progresses. Quantifying consequences to carbon dynamics and storage from die‐off events are critical for determining the current and future mitigation potential of forests. We took stand measurements five times over 2+ years from affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…The modeling experiments proposed that both the temporal change in stem size for surviving species and the replacement of vulnerable species with more drought‐tolerant ones could help increase ecosystem resilience to severe droughts, especially for ecosystems dominated by croplands with some patch grasslands/savanna ecosystems. Current field investigation also showed that drought‐induced partial mortality of living trees could stimulate the regrowth of foliage, twigs, and branches for forests that resprout (Walden et al, 2019), leading to more rapid recovery than non‐resprouters (Zeppel et al, 2015). Thus, ecosystem resilience depends on both drought severity and species composition (Gazol et al, 2018), while the speed of recovery is associated with the efficiency of repair, regrowth, and the severity of functional damage (Ruehr et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The modeling experiments proposed that both the temporal change in stem size for surviving species and the replacement of vulnerable species with more drought‐tolerant ones could help increase ecosystem resilience to severe droughts, especially for ecosystems dominated by croplands with some patch grasslands/savanna ecosystems. Current field investigation also showed that drought‐induced partial mortality of living trees could stimulate the regrowth of foliage, twigs, and branches for forests that resprout (Walden et al, 2019), leading to more rapid recovery than non‐resprouters (Zeppel et al, 2015). Thus, ecosystem resilience depends on both drought severity and species composition (Gazol et al, 2018), while the speed of recovery is associated with the efficiency of repair, regrowth, and the severity of functional damage (Ruehr et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Current field investigation also showed that drought-induced partial mortality of living trees could stimulate the regrowth of foliage, twigs, and branches for forests that resprout (Walden et al, 2019), leading to more rapid recovery than non-resprouters (Zeppel et al, 2015). Thus, ecosystem resilience depends on both drought severity and species composition (Gazol et al, 2018), while the speed of recovery is associated with the efficiency of repair, regrowth, and the severity of functional damage (Ruehr et al, 2019).…”
Section: Significance and Limitations Of Our Analysismentioning
confidence: 94%
“…Many landscape‐scale disturbances are predicted to become more frequent and severe in the coming decades (Turner, 2010; Trumbore et al ., 2015; Seidl et al ., 2017), likely driving changes in the relative abundance of seed and nonseed‐based regeneration strategies. Epicormic or apical resprouting by mature trees also limits the short‐term loss of ecosystem C relative to what occurs with mature tree mortality followed by recruitment from seed (Zeppel et al ., 2015; Walden et al ., 2019).…”
Section: Forest Regeneration Processes Critical To the Earth Systemmentioning
confidence: 99%
“…Heat waves can also have secondary or indirect effects on ecosystems (Matusick et al, 2018; Nowicki et al, 2019). For example, a heat‐wave‐and‐drought‐induced forest die‐off in southwestern Australia triggered significant loss of live standing biomass (49.3 t carbon ha −1 ; Walden et al, 2019). That forest die‐off event resulted in adult mortality and altered regeneration of a key midstorey species, Banksia grandis , indirectly affecting an important food source of an endangered cockatoo (Steel et al, 2019).…”
Section: Heat Wave Effects: Sublethal Lethal Secondary and Compoundmentioning
confidence: 99%